Operating Cost Optimization By Implementing Energy Management (Case Study In PT. Vinysea) - Budi Sulistyo, Arif; Gadre, Milind (The Indonesian Journal of Business Administration, 2017)
Abstract. PT.VINYSEA as major producer of Liquid Caustic Soda (LCS), Vinyl Chloride Monomer (VCM) and Polyvinyl Chloride (PVC) in Indonesia is affected by increment of energy cost, such as electricity and fuel price. It also leads manufacturing cost of the main products LCS, VCM and PVC are high to begin with, and tends to increase within the last 4 months, about 19%, 4% and 3% respectively. 3 research questions rise to overcome the situation. Methodology of research is conclusive positivism, since reaching decision making by applying quantitative methods of data collection and data analysis. 5C analysis technique is used to analyze business situation and identify the factors involving the view point of Competitor, Customers, Collaborators, Climate and internal Company. Assessment of 5C was conducted using fishbone diagram analysis to find out the root causes. As a solution of question no (1) Raw materials and energy sectors have big contribution by 60% and 20% respectively, (2) several actions plan to implement (i) optimization of 5 Chlor Alkali Plants’ operation load arrangement using new correlation chart, (ii) changing periodical membrane replacement at electrolysis by shorten the existing schedule, from 4 to 2 years (iii) implementation of Energy Management System. By implementing these activities. PT. VINYSEA will potentially gain cost saving 3% energy cost. Furthermore solution no (3) building own Power Plant shall be considered for long term planning. It has potential reduction about 4% operating cost. Top management shall give fully support for the implementation of recommendations, such as commitment, funding and organizationKeyword: energy, energy management, Liquid Caustic Soda, Chlor Alkali, membrane